2009 10th International Conference on Document Analysis and Recognition 2009
DOI: 10.1109/icdar.2009.79
|View full text |Cite
|
Sign up to set email alerts
|

A Steerable Directional Local Profile Technique for Extraction of Handwritten Arabic Text Lines

Abstract: In this paper, we present a new text line extraction method for handwritten Arabic documents. The proposed technique is based on a generalized adaptive local connectivity map (ALCM) using a steerable directional filter. The algorithm is designed to solve the particularly complex problems seen in handwritten documents such as fluctuating, touching or crossing text lines. The proposed algorithm consists of three steps. Firstly, a steerable filter is used to probe and determine foreground intensity along multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(45 citation statements)
references
References 8 publications
0
45
0
Order By: Relevance
“…We segment document images into lines and then into words using robust algorithm [42]. The sample results of segmented word images are shown in Figure 2.…”
Section: Keypoints Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We segment document images into lines and then into words using robust algorithm [42]. The sample results of segmented word images are shown in Figure 2.…”
Section: Keypoints Detectionmentioning
confidence: 99%
“…In the first stage, the document image is segmented into text lines and each text lines are segmented into primitive segments i.e. words using directional local profile technique [42]. The corner keypoints are extracted from word image using Harris-Laplace Corner detector.…”
Section: Bag Of Visual Words (Bovw) Frameworkmentioning
confidence: 99%
“…Shi et al [16] suggested a method based on adaptive local connectivity map (ALCM) using steerable directional filter for extracting handwritten Arabic text. Firstly, steerable filter is applied to the document image and it is converted into ALCM.…”
Section: International Journal Of Computer Applications (0975 -8887) mentioning
confidence: 99%
“…A method was proposed in [9] that uses ALCM algorithm which gives a mask corresponding to text line locations. Then, the text lines are extracted by superimposing the components with text line pattern mask.…”
Section: Introductionmentioning
confidence: 99%